Action research in business and management - Coghlan, David; Shani, Abraham B. (Fundamentals of Applied Research, 2016)
This Major Work, for the first time, brings together the diverse publications in action research in business and management since the 1950s. Designed to be a foundation resource for individual scholars and business schools, this collection provides academics in the field with a touchstone resource to help build their knowledge and understanding of the field. The volumes have been put together by two internationally-renowned editors, and the introductory chapter further explores how the material in the set extends and changes our understanding of the development of the field, and the contributions of key people and ideas within it